Applications of Dendrimers in Drug Delivery Agents, Diagnosis, Therapy, and Detection. (15th April 2014) - Noriega-Luna, B.; Godínez, Luis A.; Rodríguez, Francisco J.; Rodríguez, A.; Zaldívar-Lelo de Larrea, G.; Sosa-Ferreyra, C. F.; Mercado-Curiel, R. F.; Manríquez, J.; Bustos, E.
Abstract : In recent years, the application of dendrimers in biomedicine attracted much attention from scientists. Dendrimers are interesting for biomedical applications because of their characteristics, including: a hyperbranching, well-defined globular structures, excellent structural uniformity, multivalency, variable chemical composition, and high biological compatibility. In particular, the three-dimensional architecture of dendrimers can incorporate a variety of biologically active agents to form biologically active conjugates. This review of dendrimers focuses on their use as protein mimics, drug delivery agents, anticancer and antiviral therapeutics, and in biomedical diagnostic applications such as chemically modified electrodes.